Do Canadian collegiate hockey players accurately perceive body composition changes after unmonitored training and diet? - Prokop, N. W.; Duncan, L. R.; Andersen, R. E. (Applied Physiology, Nutrition, and Metabolism, 2015)
Collegiate athletes often use nutritional programs and supplements to elicit body composition changes in muscle or fat. It is unknown if athletes can accurately perceive their fluctuations in body composition, yet their understanding may help them make more accurate interpretations regarding the success of potential nutrition or exercise regimens. The purpose of this study was to investigate if collegiate hockey players could accurately perceive a change in body composition during a 3-month period within their regular season, in which no predetermined nutritional or exercise program was provided. Twenty-four male Canadian collegiate hockey players completed preseason and midseason body composition assessments using dual-energy X-ray absorptiometry. Immediately before the midseason scan, players attempted to accurately match their perceived fluctuation in composition, with predetermined categorical ranges of relative body composition and strength. Two-thirds of players and one-half of players accurately perceived changes in arm-lean and arm-fat tissue, respectively. Approximately two-thirds of players did not accurately perceive gains or losses of lean or fat tissue within their leg and overall body. Although some athletes partially detected changes in the lean and fat tissue of particular regions, the vast majority of players cannot detect the type, or amount of tissue gained and lost across the overall body. Body composition assessments, rather than an athlete`s perceptions, should be used to help interpret the success of a sport nutrition or exercise program. Athletes should be aware that physiologic adaptations might take place unnoticed, which could affect the acceptance and adherence of nutrition or exercise interventions.